Modelling catchment scale response to drought risk, a case study in South Africa. - Lulane, Zanele (Cranfield University, 2021)
South Africa is a water scarce country with future water availability threatened by climate change, an increasing population leading to urbanization, increasing agricultural production, and industrialization. Past droughts have highlighted the country’s vulnerability to drought leading to economic losses in the Agricultural sector, inadequate water, and supply for basic domestic needs and failure to meet ecological water requirements. A case study was carried out in the water scarce, 4,937 km² agricultural intensive Groot Letaba catchment located in the Limpopo province. Water Evaluation and Planning (WEAP) model was used to simulate the water supply system in the catchment, from 1981 to 2016. The Nash–Sutcliffe Efficiency was used to validate the model’s accuracy providing a value of 0.91 and 0.86 during calibration (1981-2000) and 0.69 and 0.65 during validation (2001-2016) for streamflow and Tzaneen reservoir levels, respectively. A reference scenario to assess water resources and water demand sites’ vulnerability should droughts experienced between 1981 to 2016 be repeated under current demand was developed. 10% Agricultural water supply reduction, 50% per capita use rate reduction, Tzaneen reservoir storage increase and rerouting domestic return flow to the river were explored as drought adaptation measures. Drought response measures prevented reservoir drawdown in moderate droughts and delayed drawdown in severe droughts, reducing their temporal extents. Improvements in water resources availability correlated with improving demand coverage and reliability. Pairing drought response scenarios amplified benefits realized resulting in 100% demand coverage and reliability for two demand sites. All drought response measures were insufficient to fully circumvent droughts with a magnitude like the 1992-1996 drought. These findings show that effectiveness of response measures is dependent on the intensity and duration of the drought.
Keywords: Drought risk; WEAP; Groot letaba; drought response